Granulocytic Sarcoma in an Adult with Relapsed Acute Myeloid Leukaemia - Neethu Ann Kurien (Journal of Clinical and Diagnostic Research, 2016)
Granulocytic sarcoma is an extramedullary tumour consisting of malignant granulocytic precursor cells that is common among children with acute myeloid leukaemia (AML). We report a case of orbital granulocytic sarcoma in an adult with relapsed undifferentiated AML–M0. It presented as bilateral medial canthal swellings. An incisional biopsy confirmed the diagnosis of granulocytic sarcoma. The swelling resolved with re-induction chemotherapy.